2021
DOI: 10.1007/s12198-020-00227-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the U.S. domestic air transportation network: temporal evolution of network topology and robustness from 2001 to 2016

Abstract: The U.S. air transportation network (ATN) is critical to the mobility and the functioning of the United States. It is thus necessary to ensure that it is well-connected, efficient, robust, and secure. Despite extensive research on its topology, the temporal evolution of the network's robustness remains largely unexplored. In the present paper, a methodology is proposed to identify long-term trends in the evolution of the network's topology and robustness over time. The study of the U.S. domestic ATN's robustne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In Cheung and Gunes ( 2012 ) the authors analyze its evolution over the period 1991–2011, and the study reported in Siozos-Rousoulis et al. ( 2021 ) concerns the period 2001–2016. Overall, one does not observe considerable changes in the topological properties of the networks.…”
Section: Litterature Reviewmentioning
confidence: 99%
“…In Cheung and Gunes ( 2012 ) the authors analyze its evolution over the period 1991–2011, and the study reported in Siozos-Rousoulis et al. ( 2021 ) concerns the period 2001–2016. Overall, one does not observe considerable changes in the topological properties of the networks.…”
Section: Litterature Reviewmentioning
confidence: 99%
“… Zhou et al (2019a) Weighted network efficiency Australia, Brazil, Canada, China, E.U., India, Russia, U.S. Chen et al (2020) Size of giant component, size of isolated clusters, network efficiency China Wandelt et al (2021) Size of giant component Worldwide Network structure evolution Lin and Ban (2014) Degree, betweenness, average path length, clustering coefficient, network efficiency U.S. (1990–2010) Wang et al (2014) Degree, betweenness, closeness, average path length, clustering coefficient, density, diameter China (1930–2012) Wandelt and Sun (2015) Degree, betweenness, average path length, clustering coefficient, density The entire world at country level (2002–2013) Dai et al (2018) Degree, average path length, clustering coefficient, core Southeast Asia (1979–2012) Wandelt et al (2019) Degree, average path length, clustering coefficient, assortativity Australia, Brazil, Canada, China, India, Russia, U.S., E.U. (2002–2013) Cheung et al (2020) Degree, betweenness, closeness, eigenvector, regional importance Worldwide (2006–2016) Siozos-Rousoulis et al (2021) Degree, betweenness, average path length, clustering coefficient, assortativity, network efficiency U.S. (2001–2016) …”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper incrementally contributes to the literature on air transportation network (ATN) structure analysis. Specifically, the existing literature ( Allroggen et al, 2015 ; Cheung et al, 2020 ; Dai et al, 2018 ; Lin and Ban, 2014 ; Siozos-Rousoulis et al, 2021 ; Wandelt and Sun, 2015 ; Wang et al, 2014 ) has investigated the long-term evolution of ATNs along with economic development. On the contrary, our study focuses on the dynamic short-term variation of the WATN induced by COVID-19, including decline and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial hazards, such as the Eyjafjallajökull volcano eruption in 2010, have led to airspace closures and several research studies have discussed the impact of the closure and its side-effects on the European aviation system ( Budd et al, 2011 , Miller, 2011 , Bolić and Sivčev, 2011 , Wilkinson et al, 2012 , Alexander, 2013 , Luchkova et al, 2015 , Reichardt et al, 2019 ). Complex network representations of the aviation system have widely analyzed the centrality of individual airports (or groups of airports) under random failure and intentional attack scenarios ( Cardillo et al, 2013 , Janić, 2015 , Wandelt et al, 2015 , Dunn and Wilkinson, 2016 , Voltes-Dorta et al, 2017 , Clark et al, 2018 , Sun et al, 2020 , Janić, 2021 , Siozos-Rousoulis et al, 2021 ). Finally, the recent developments around the COVID-19 pandemic have led to studies which analyze the resilience of the aviation system towards health/epidemiology-related disruptions ( Nikolaou and Dimitriou, 2020 , Zhou et al, 2021b , Bombelli, 2020 , Zhou et al, 2021a , Kuo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%